KNOWLEDGE OF HEALTH CARE WORKERS TOWARDS THE MANAGEMENT OF SEVERE ACUTE MALNUTRITION IN INFANTS UNDER SIX MONTHS IN ADJUMANI HOSPITAL UGANDA. A CROSS-SECTIONAL STUDY. - Baru, Joshua; Kungu, Joseph; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2024)
Background In Adjuman Hospital, there is limited knowledge among health workers understanding the nutritional treatment of SAM. This study aimed to determine the level of Knowledge of Health workers on the management of SAM among infants under 6 months of age at Adjumani Hospital. Methodology This was a cross-sectional study among 45 health workers at the hospital. Data was collected on participant demographics and knowledge factors using the Questionnaire and Key informant guide for qualitative data. Data was coded and entered into SPSS V 20 and analyzed. Qualitative data was transcribed as text, analyzed thematically, and presented according to major emerging themes. Results Most respondents were female (62.2%), 55.6% of the participants were aged (30-38) and 44.4% were diploma holders. (86.7%) of the respondents stated that they were trained in the management of SAM, (97.8%) of the participants had high Awareness about standard written guidelines to follow in the management of children with SAM, 40 % of the participants stated that their Source of information about SAM, if not trained, was through self-study and 80% of the participants mentioned correct answers that Children with SAM need to be kept dry and warm during the day and night to prevent hypothermia. Conclusion There is a high level of clinical knowledge on the management of SAM among health workers at Adjumani Hospital as evidenced by both quantitative and qualitative evidence even though most of the respondents interviewed were lower categories of health workers. Recommendations There is a need to intensify continuous medical education among staff. Knowledge of good nutrition is expected to result in better clinical practices.